Tourism destination management in a post-pandemic context : global issues and destination management solutions - Gowreesunkar, Vanessa GB (Tourism security-safety and post conflict destinations, 2021)
2020 has left an indelible mark on the history of travel and tourism worldwide leaving tourist destinations with long-term lessons to learn from the impacts of COVID-19. Tourism destinations are looking for new guidelines and original research that offer management solutions to deal with the damage wrought by the pandemic. Tourism Destination Management in a Post-Pandemic Context gives an enriching insight into the issues and challenges faced by tourism destinations during and after the pandemic, exposing emerging trends and proposing novel management solutions in order to develop coping capacities of destinations and build resilience against the effects of potential future pandemics Drawing on lessons of the COVID-19 pandemic, this expansive collection presents cases and competency frameworks to advance theoretical and empirical knowledge in the management of destinations post-pandemic.